2020
DOI: 10.3168/jds.2019-18011
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Pure-breeding with sexed semen and crossbreeding with semen from double-muscled sires to improve beef production from dairy herds: Weight and value of calves

Abstract: The use of sexed semen to produce purebred replacement heifers allows a large proportion of dairy cows to be mated to double-muscled sires and for quantitative and qualitative improvements to be made to beef production from dairy herds. A survey of 1,285 crossbred calves showed that they are destined not only for veal production (like purebred dairy calves) but also for beef production. Crossbred calves obtained from Belgian Blue sires (sold on average at 34 d of age and 64 kg of weight) had a higher market va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In the conditions that prevail in countries with beef markets that favor lean, muscular carcasses, the higher value of crossbred calves, especially from double-muscled sires, is a much more important factor (Dal Zotto et al, 2009). In this project (Bittante et al, 2020), the beef crossbred bull and heifer calves were sold by dairy farmers to intensive veal and beef fatteners at an average of €318/calf at 5 wk of age (63 kg of live weight) against a price of €80 to €100/calf for dairy bull calves of the same age (ISMEA, 2019). The average price of Belgian Blue × Holstein-Friesian calves was €363/calf, an increase equivalent to the price of about 800 L of milk over the price of a purebred dairy bull calf.…”
Section: Combined Use Of Sexed Semen and Beef Semen To Increase The Profitability Of Dairy Farmsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the conditions that prevail in countries with beef markets that favor lean, muscular carcasses, the higher value of crossbred calves, especially from double-muscled sires, is a much more important factor (Dal Zotto et al, 2009). In this project (Bittante et al, 2020), the beef crossbred bull and heifer calves were sold by dairy farmers to intensive veal and beef fatteners at an average of €318/calf at 5 wk of age (63 kg of live weight) against a price of €80 to €100/calf for dairy bull calves of the same age (ISMEA, 2019). The average price of Belgian Blue × Holstein-Friesian calves was €363/calf, an increase equivalent to the price of about 800 L of milk over the price of a purebred dairy bull calf.…”
Section: Combined Use Of Sexed Semen and Beef Semen To Increase The Profitability Of Dairy Farmsmentioning
confidence: 95%
“…Omission of maternal ease of calving in the selection index of the Belgian Blue has led to a rapid improvement in their beef traits and reduced sexual dimorphism (Bittante et al, 2018). This may explain the greater preference on the part of the farmers involved in this project for Belgian Blue semen (Bittante et al, 2020) over other double-muscled breeds (Piedmontese and INRA 95) and conventional beef breeds (Limousin and Simmental).…”
Section: Effects Of the Use Of Semen Of Different Beef And Dairy Breeds On The Conception Rate Of Cows And Heifersmentioning
confidence: 99%
“…These data were not available for calves retained and fattened by the dairy farmers, but their outcomes were recorded by ARAV. Data on the characteristics of the crossbred calves sold by dairy farmers are reported and discussed in a previous paper (Bittante et al, 2020b).…”
Section: Gathering Data On Calves Sold By Dairy Farmersmentioning
confidence: 99%
“…Moreover, the second study of the MeetBULL project showed that, in the Italian market conditions, crossbred calves sold at about 5 wk of age had a value on average 3 to 4 times that of purebred dairy calves (Bittante et al, 2020b). Slightly higher prices were fetched for males than females, and for calves born from Simmental cows than calves from specialized dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…Sexed semen use can overcome the economic and welfare issues of low value male dairy calves and enhance calf sales revenue through use of beef semen on cows of lower genetic value not selected for breeding dairy herd replacements (Bittante et al, 2020). However, despite the potential benefits, adoption of SS has been hindered in seasonal pasture-based systems as a reduced P/AI negatively affects the compactness of the calving period, a major driver of profitability (Hutchinson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%